Estudio de factibilidad para la creación de una Agencia de Marketing Digital en la ciudad de Latacunga. - Nicolalde Vaca, Alex Ricardo (2021)
The pandemic pushes us towards a new digital revolution, the synergistic nature of new technologies will mark the productive and communicational processes of our era worldwide. The above mentioned gives rise to an important opportunity to implement a Digital Marketing Agency, focused on entrepreneurs and SMEs located in the canton of Latacunga. This document presents the Feasibility Study of the project to determine its viability; for the Market Study we took the database of the affiliates of the Latacunga Chamber of Commerce, and as a result of the calculation of the sample, 246 members were surveyed, the focus of the research was considered the inductive method as our main tool to obtain information and the quantitative method to collect and analyze data, with the data collection instrument the preferences and needs of our target market were determined, identifying an unsatisfied demand for our services; the Technical Study, the appropriate size, location, selection of technologies and necessary resources are determined for the agency's operation, as a result, the installed and used capacity that we could cover was obtained, being 60% for the first year; in the Organizational Study, the hierarchical structure is defined with the responsibilities and positions that each collaborator must fulfill and the manual of their functions; the Economic-Financial Study shows the costs and expenses in investments to guarantee the operation of the company, through the financial evaluation indicators, the profit in a 5-year period (NPV) of $ 28,952.53 was determined and that the recovery period ( PRI) is one year, 5 months and 12 days, at an internal rate of return (IRR) of 39.97%, with a benefit-cost ratio of $ 1.47 for every $ 1.00 invested. Finally, it is concluded that the profitability of the implementation of the Digital Marketing Agency is viable.